Einstein's Rocket Ship, the Deflection of Light and the Precession of the Orbital Perihelion - Firmin J. Oliveira (European Scientific Journal, ESJ, 2018)
The nature of the principle of equivalence is explored. The light ray travel path in an accelerated reference frame, a rocket ship, is described and the rocket ship model is used to derive the deflection of light by a massive body. By accounting for the effect of the velocity of the accelerated observer relative to an inertial frame, the additional deflection angle is obtained due to the aberration of the light beam. This model is applied to the deflection of light by a central gravitational field, giving the total deflection angle in agreement with the standard result. Also, a novel approach is given by considering the deflection of light by a massive body to obtain the precession of the perihelion of a planet.